2007
DOI: 10.1007/s11832-007-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Abduction pillow immobilization following hip surgery: A welcome alternative for selected patients

Abstract: Background Studies have shown that when using a spica cast following hip surgery in children , there are associated complications such as soiling, pressure sores, and osteopenic fractures. Methods Charts were retrospectively reviewed for all patients who had undergone hip surgeries by one surgeon at one institution between 1999 and 2005. The method of post-operative immobilization (spica cast or abduction pillow) and complications were recorded for each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“… 3 , 11 It’s been suggested that hip spica casting be reserved for children with poor bone quality or those at risk of implant failure. 3 , 7 , 17 Our findings are consistent with this as surgeons reported they would choose increased immobilization with increasing patient complexity, including surgery in children at GMFCS level V, bilateral surgery, and an open reduction. The use of a hip spica cast increased from 7% in case 1 to 21% in case 2 with the addition of a PO and/or an open reduction.…”
Section: Discussionsupporting
confidence: 85%
“… 3 , 11 It’s been suggested that hip spica casting be reserved for children with poor bone quality or those at risk of implant failure. 3 , 7 , 17 Our findings are consistent with this as surgeons reported they would choose increased immobilization with increasing patient complexity, including surgery in children at GMFCS level V, bilateral surgery, and an open reduction. The use of a hip spica cast increased from 7% in case 1 to 21% in case 2 with the addition of a PO and/or an open reduction.…”
Section: Discussionsupporting
confidence: 85%
“…Spica casts have been actively avoided by families and care teams familiar with them because they are cumbersome and associated with other challenges during care ( 26 ). Albrektson et al compared the two methods in a retrospective review of 21 patients with CP or other genetic syndromes undergoing hip surgery and concluded that spica casts should be used in patients with osteopenia or instability in the early post-operative period ( 21 ). Truong et al demonstrated similar pain and complication profiles in children treated in spica casts versus short leg casts linked with a bar ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, post-operative immobilization has most commonly included hip spica casting (Figure 2A) (11,15,19). Theoretical advantages of casting include stability of the bony reconstruction prior to bony union, maintenance of articular alignment, and protection of incisions, and as such some surgeons utilize them in patients with poor bone quality or if there is concern for the fixation achieved intraoperatively (17,(19)(20)(21). There are known postoperative complications when using hip spica casts, including skin sores, hygiene difficulties, need for specialized car seats, wheelchair challenges, prolonged anesthesia time, and psychosocial impacts on both the patient and their family (22).…”
Section: Introductionmentioning
confidence: 99%
“…Lubicky et al did not detect meaningful differences in complication rates between spica casting and "no immobilization" after spastic hip reconstruction, but Ruzbarsky et al reviewed 93 hip reconstructions and found spica casting to be an independent risk factor for perioperative complications [11,21]. Immediate mobilization has been reported with low complication rates after neuromuscular hip reconstruction, as has the use of an abduction pillow [20,29]. Our complication rates are comparable to previous reports, wherein medical complications in cerebral palsy and decubitus ulcers are considered common regardless of the reason for spica cast application [10][11][12]21].…”
Section: Discussionmentioning
confidence: 99%